"WHITE ELEPHANT" IN UKRAINIAN CARPATHIANS MOUNTAINS: ON RESTORATION OF A FORMER MILITARY ASTRONOMICAL-METEOROLOGICAL OBSERVATORY - Смирнов, І.; Левінськова, Н. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2018)
The article deals with the fate of the astronomical-meteorological observatory, which was built in the Eastern Carpathеs on the Hill of Pip-Ivan (height 2028 m) in 1938, when the Carpathian region was part of Poland. Another name of the observatory is "White Elephant", because in the winter under the snow the observatory’s house resembles the shape of the elephant. Mount Pip Ivan has a pyramidal shape with the presence of ancient forms of glacial relief, composed of sandstone. The observatory was equipped with the most up-to-date scientific equipment, in particular, a telescope, astrograph and refractor of British production. The Observatory was destroyed during the Second World War. Currently, with joint efforts of Ukraine and Poland, in particular with the participation of the University of Warsaw and the Precarpathian University named after V. Stefanyk of Ivano-Frankivsk the restoration of the observatory is under way, as well as the construction of an International Center for Ukrainian and Polish Students Youth Meetings focusing on research in geography, meteorology, geology, seismology, astronomy and biology. Keywords: astronomical-meteorological observatory, Mount Pіp Ivan, restoration, Obserwatorium fund, research in the fields of geography, meteorology, geology, seismology, astronomy and biology.